2021
DOI: 10.3390/pharmacy9040189
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Inappropriate Medication Prescribing Detected by Computer Algorithm among Older Patients: Results from the MAPT Study

Abstract: (1) Background: Some medications may be dangerous for older patients. Potentially inappropriate medication prescribing (PIP) among older patients represents a significant cause of morbidity. The aim of this study was to create an algorithm to detect PIP in a geriatric database (Multidomain Alzheimer Preventive Trial (MAPT) study), and then to assess the algorithm construct validity by comparing the prevalence of PIP and associated factors with literature data. (2) Methods: An algorithm was constructed to detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…St. 28) and the START and STOPP criteria (O'Mahony et al, 2015) have been given most attention, the NORGEP-NH criteria seem to be a more appropriate choice for Norwegian nursing home residents, especially as these validated criteria are based on nationally available medications (Nyborg et al, 2015). A few pharmacist-led studies have electronically identified the prevalence of inappropriate prescribing in nursing homes residents and older adults (Pagès et al, 2021). The findings of these studies are comparable to clinical studies, which also state that the use of inappropriate medications by these residents is highly prevalent.…”
Section: Healthcare Levelmentioning
confidence: 99%
“…St. 28) and the START and STOPP criteria (O'Mahony et al, 2015) have been given most attention, the NORGEP-NH criteria seem to be a more appropriate choice for Norwegian nursing home residents, especially as these validated criteria are based on nationally available medications (Nyborg et al, 2015). A few pharmacist-led studies have electronically identified the prevalence of inappropriate prescribing in nursing homes residents and older adults (Pagès et al, 2021). The findings of these studies are comparable to clinical studies, which also state that the use of inappropriate medications by these residents is highly prevalent.…”
Section: Healthcare Levelmentioning
confidence: 99%
“…Previous cross-sectional studies have already revealed that receiving Lvm in dementia was associated with lower HRQoL and an increased risk for hospitalization and greater health care expenditures. 15,16,20,21 However, the longitudinal effects of Lvm on patient-relevant outcomes have been rarely reported. Therefore, the objective of the present analysis was to examine the effects of receiving Lvm on HRQoL, hospitalization and health care expenditures for PwD over 24 months.…”
Section: Introductionmentioning
confidence: 99%
“…Previous cross‐sectional studies have already revealed that receiving Lvm in dementia was associated with lower HRQoL and an increased risk for hospitalization and greater health care expenditures 15,16,20,21 . However, the longitudinal effects of Lvm on patient‐relevant outcomes have been rarely reported.…”
Section: Introductionmentioning
confidence: 99%